2014
DOI: 10.1186/1742-4690-11-s1-p133
|View full text |Cite
|
Sign up to set email alerts
|

Naturally occurring protease inhibitor resistance mutations and their frequencies in HIV proviral sequences of drug-naïve sex workers in Nairobi, Kenya

Abstract: Sub-Saharan Africa accounts for 69% of the people living with HIV globally. An estimated 1,600,000 Kenyans are living with HIV-1. Antiretroviral therapy (ART) has saved 9 million life-years in Sub-Saharan Africa. However, drug resistance mutations reduce the effectiveness of ART, and need to be monitored for effective ART. Naturally occurring primary antiretroviral drug resistance mutations have not been well analyzed in ART naïve HIV+ patients in Kenya. Here we have examined protease inhibitor (PI) resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
3
1
Order By: Relevance
“…Previous related studies [ 3 - 15 ] identified some of the mutations that were identified in this study, however, our study reports other several new mutations of clinical importance which were not reported in the previous studies. The existence of these new mutations that encode resistance to the present drugs the participants are currently undertaking.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Previous related studies [ 3 - 15 ] identified some of the mutations that were identified in this study, however, our study reports other several new mutations of clinical importance which were not reported in the previous studies. The existence of these new mutations that encode resistance to the present drugs the participants are currently undertaking.…”
Section: Discussioncontrasting
confidence: 58%
“…In Kenya, mutations conferring resistance to available ARVs has been reported in past studies. These mutations included M184V, K65R,D67N,K70R,K219Q,Q151M, T215F, M41L, T69N, V75M, M41L, T69N, V75M, D67G, V75M, M184I, T215N, M41LM, T215N, K219N,210W, T215Y as NRTIs; K103N/S, Y181C/Y/I/V, G190A/S, L100I,V179T, V106I/A, V108I, P225H, M230L, K238T, P225H, F227L as NNRTIs; M46I/L, D30N,M46I,V82F,L90M as PIs [ 3 - 15 ]. However, these studies did not link the mutations with the viral tallies and ARVs the participants were taking.…”
Section: Introductionmentioning
confidence: 99%
“…10,23–29 Consistent with our findings, other studies have reported high PDR levels (10%–48%) among FSWs in different countries, including those in sub-Saharan Africa. 28,30–34 Moreover, previous studies also have shown a higher PDR rate among communities and groups with high-risk behaviors. 29,35 This highlights the vulnerability of FSWs to HIVDR and the risk of onward transmission to the general population.…”
Section: Discussionmentioning
confidence: 94%
“…Regular surveillance for HIVDR in key affected groups such as SWs, is not routinely undertaken in South Africa, and available evidence globally is based upon very small samples from only a few locations. Amongst SW populations within Kenya, evidence suggests a 22% prevalence of HIVDR [ 21 ]. An unpublished Kenyan study suggested that 8.3% of ARV treated FSWs within the Pumwani cohort had HIVDR (5/60)[ 22 ].…”
Section: Introductionmentioning
confidence: 99%